2016
DOI: 10.1111/risa.12635
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Risk Perception of Household Cleaning and Washing Products

Abstract: A large share of accidental and nonaccidental poisonings are caused by household cleaning and washing products, such as drain cleaner or laundry detergent. The main goal of this article was to investigate consumers' risk perception and misconceptions of a variety of cleaning and washing products in order to inform future risk communication efforts. For this, a sorting task including 33 commonly available household cleaning and washing products was implemented. A total of 60 female consumers were asked to place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 37 publications
1
21
0
1
Order By: Relevance
“…In line with the natural-is-better heuristic, synthetic chemicals are much more negatively perceived compared with chemicals of natural origin (Saleh et al, 2019;. This perception results in a biased risk perception of cleaning products with an "eco" label on it (Bearth, Miesler, & Siegrist, 2017). For example, people evaluated an "eco" drain cleaner as much safer compared with a regular drain cleaner, despite the two products containing very similar ingredients.…”
Section: The Natural-is-better Heuristicmentioning
confidence: 99%
“…In line with the natural-is-better heuristic, synthetic chemicals are much more negatively perceived compared with chemicals of natural origin (Saleh et al, 2019;. This perception results in a biased risk perception of cleaning products with an "eco" label on it (Bearth, Miesler, & Siegrist, 2017). For example, people evaluated an "eco" drain cleaner as much safer compared with a regular drain cleaner, despite the two products containing very similar ingredients.…”
Section: The Natural-is-better Heuristicmentioning
confidence: 99%
“…For products containing chemicals, consumers might regard irrelevant cues featured on a given product's labeling as indicators of its risk level. For example, eco‐labeled cleaning products are generally perceived as being safer than conventional cleaning products, which might lead to individuals being less careful in terms of using these products (Bearth et al., ). This indicates that consumers might not always, or solely, refer to the textual and graphical safety information featured on the packaging of products when judging the risks associated with those products (Bearth et al., ; Hinks et al., ; Riley, Fischhoff, Small, & Fischbeck, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Additionally, previous studies have shown that laypeople often perceive “natural” chemicals more positively, meaning that they are considered to be less risky when compared to synthetic chemicals (Hartmann, Hübner, & Siegrist, ; Rozin et al., ; Rozin, Fischler, & Shields‐Argeles, ; Siegrist, Hübner, & Hartmann, ). Moreover, other studies have investigated consumers’ risk perceptions concerning chemicals and their preferences for natural products, particularly chemicals found in food and household cleaning products (Bearth, Miesler, & Siegrist, ; Dickson‐Spillmann, Siegrist, & Keller, ; Kraus et al., ). Furthermore, it has been suggested that chemophobia, which is defined as the irrational fear of chemicals, could fuel laypeople's negative perceptions of chemical‐containing products and their fear of synthetic chemicals (Entine, ; Francl, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This factor could be one explanation why the public in comparison with experts is much more concerned about gene technology, for example . A risk perception study showed that laypeople, but not experts, regard ecocleaning products as safer than their regular counterparts . This finding further suggests that laypeople's risk perceptions may be influenced by product attributes that are unrelated to the risks associated with the products.…”
Section: Introductionmentioning
confidence: 99%